Securing Fixed Orthodontic Components With Vinyl Polysiloxane for Ease During Orthognathic Surgery. Issue 1 (January 2022) - Ram, RSVM Raghu; Ranganayakulu, I; Viswanadh, K Anand
Unease from brackets, archwires, and ligature ties during orthognathic surgery makes oral and maxillofacial surgeons to distract from their work field, which in turn makes precise maneuvering and fixation of the jaws challenging. The present article describes a simple, useful clinical tip which eliminates the above problem by covering the fixed orthodontic components using vinyl polysiloxane impression material (putty).